Visual Coverage of War on Terror in Pakistani English Newspapers - Sami Ullah; Adiba Akhter; Syed Inam ur Rahman (ASIAN Journal of International Peace & Security (AJIPS), 2021)
According to peace scholar Johan Gultung war journalism frame highlights the differences between the conflict parties and promotes violence as a tool to conflict resolution while in his views peace journalism frames highlight the peace as a first step in its coverage and bring down differences between the war parties to resolve the conflict. Therefore, on the classification of peace scholar of these two competing frames, this study tried to investigate the news photographs of the war quantitatively (2014-2015), of ongoing war on terror in Pakistan using war photographs. The current study examined that to which extent the news photographs of war are framed in war versus peace journalism in the two leading dailies of Pakistan Dawn (English) and Jung (Urdu). Findings of this study also indicated that both the newspapers provided war photographs in different assortments while covering the conflict in the country which proves that photograph selection in terms of war versus peace journalism had a very concrete touch on public opinion influencing the perception of news.